An unusual radiological presentation of pulmonary Langerhans' cell histiocytosis. (3rd July 2012) - Burr, Lucy; Fanning, Steven; Wong, David; Bowler, Simon
Abstract : Langerhans' cell histiocytosis is a proliferative disease of the dendritic cell lineage. It usually has a characteristic radiological presentation of apical nodules and small cysts occurring predominantly in young adult smokers. Here we report a case of multisystem Langerhans cell histiocytosis in a 75-year-old woman with unusual chest radiology.